2021
DOI: 10.3390/pharmaceutics13040536
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Visualization of 161Tb- and 177Lu-Labeled Somatostatin Analogues Using Dual-Isotope SPECT Imaging

Abstract: The decay of terbium-161 results in the emission of β¯-particles as well as conversion and Auger electrons, which makes terbium-161 interesting for therapeutic purposes. The aim of this study was to use dual-isotope SPECT imaging in order to demonstrate visually that terbium-161 and lutetium-177 are interchangeable without compromising the pharmacokinetic profile of the radiopharmaceutical. The 161Tb- and 177Lu-labeled somatostatin (SST) analogues DOTATOC (agonist) and DOTA-LM3 (antagonist) were tested in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
7
27
0
1
Order By: Relevance
“…Tumor cell uptake and localization DOTA-LM3, irrespective of whether it was labeled with terbium-161 or lutetium-177 [43], showed the highest AR42J tumor cell uptake in vitro with ~70% of total added activity after a 2-h incubation period. This was 4-to sixfold higher than the uptake of radiolabeled DOTATOC (~ 10%) and DOTATOC-NLS (~ 15%), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tumor cell uptake and localization DOTA-LM3, irrespective of whether it was labeled with terbium-161 or lutetium-177 [43], showed the highest AR42J tumor cell uptake in vitro with ~70% of total added activity after a 2-h incubation period. This was 4-to sixfold higher than the uptake of radiolabeled DOTATOC (~ 10%) and DOTATOC-NLS (~ 15%), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since it was previously confirmed that the SST analogues have equal in vitro and in vivo behavior regarding (sub)cellular uptake and tissue distribution, irrespective of whether they were labeled with lutetium-177 or terbium-161 [43], those experiments were performed with only one version of the radiolabeled peptides.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations